Analyzing the Effects of Internet Banking on the Efficiency of Commercial Banks in Uganda. - Charity .A. Bongomin (Uganda Christian University, 2023)
The banking industry has been largely influenced by technological advancements just like the other aspects of life. With the emergence of e-banking, bank operations have been significantly redefined and transformed. Technology is viewed as one of if not the major driving force in the performance success of firms. All banks irrespective of whether local or foreign are heavily investing on the different emerging technologies so as to assure that their customers are satisfied with their services. This study sought to analyze the effects of internet banking on the efficiency of commercial banks in Uganda, using Stanbic bank as the case study. Internet banking in the study being the independent variable and bank efficiency being the dependent variable. The study was guided by different objectives and these were, examini9ng the types of e-banking services provided by Stanbic bank, evaluating the effectiveness of internet banking methods employed by Stanbic bank, establishing the possible challenges of internet banking in Stanbic bank and establishing how the efficiency of commercial banks has been influenced by internet banking. The study was carried out using a cross-sectional research design that was descriptive. Both qualitative and quantitative methods were used as main methods and under qualitative the responses were derived from the respondents. Bank efficiency in this case was measured through the reliability of the bank, its response to its customers, and the level of customer satisfaction as well. The results revealed that there is a good standing relationship between the two variables, internet banking being the independent variable and efficiency being the dependent. According to the measures used to measure the banks efficiency, the reliability levels the customers have on the banks is good, just as the timely responses delivered to the customers in case of any concern or inquiry and all these are done on time. The satisfaction of the customers towards everything is also good. The study disclosed that the efficiency levels of the bank are good and also there is a relatively strong relationship between internet banking and bank efficiency. The study recommends that more multiple measures should be put in place to enhance internet banking among commercial banks which will lead to the improvement of efficiency. It also recommends that internet banking should be invested in and the government through favorable policies should generate and create a conducive environment for commercial banks to operate seeing as their growth will encourage and lead to economic growth of the country.
This is a dissertation.